Compiler Construction c - O$1 (BBoyle, Michael.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the 21st International Conference on Compiler Construction, CC 2012, held as part of the joint European Conference on Theory and Practice of Software, ETAPS 2012, which took place in Tallinn, Estonia, in March/April 2012. The 13 papers presented in this book were carefully reviewed and selected from 51 submissions. They are organized in topical sections named: GPU optimisation, program analysis, objects and components, and dynamic analysis and runtime support.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Computer Communication Networks; Algorithm Analysis and Problem Complexity